EVALUATION OF LONG TERM OUTCOMES ASSOCIATED WITH PRETERM EXPOSURE TO ANTENATAL CORTICOSTEROIDS : A SYSTEMATIC REVIEW - Rajagukguk, Rio Martin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The aim: This study aims to show about evaluation of long term outcomes associated with preterm exposure to antenatal corticosteroids.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up to date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 117 articles, whereas the results of our search on SagePub brought up 112 articles. The results of the search conducted for the last year of 2013 yielded a total 91 articles for PubMed and 66 articles for SagePub. The result from title screening, a total 2 articles for PubMed and 11 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria.Conclusion: Numerous studies have shown no evidence of long-term harm (and in fact showed improved survival and neurodevelopmental outcomes with long-term pulmonary and others benefit), particulary as it relates to a single course of corticosteroids administered at less than 34 weeks of gestation.